2014
DOI: 10.1007/s11524-014-9879-2
|View full text |Cite
|
Sign up to set email alerts
|

A Capacity Building Approach to Increase Sports Participation in Disadvantaged Urban Communities: A Multilevel Analysis

Abstract: Recent evidence showed that community capacity building is one of the key methods to reach health improvements within disadvantaged communities. Physical activity and sports participation are important means to reach health improvements. This study investigates a capacity building method which aims at increasing sports participation in the community, especially for individuals at higher risk of sports deprivation. The main aims of the present study, are the following: (1) to examine differences in sports parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 23 publications
0
26
0
Order By: Relevance
“…In terms of facilitators of sports participation much of the current literature focuses on more specific barriers such as those faced by people with physical disability, visual impairment, or those in economically disadvantaged areas [ 24 26 ]. There are few current studies which examine facilitators in the more general population [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of facilitators of sports participation much of the current literature focuses on more specific barriers such as those faced by people with physical disability, visual impairment, or those in economically disadvantaged areas [ 24 26 ]. There are few current studies which examine facilitators in the more general population [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…While our review focused on capacity building in a specific field of research (PA promotion among older adults), our understanding of capacity building strategies might benefit from findings from other fields beyond our focus. For example, Marlier et al [ 41 ] compared communities enhancing their capacity through community coalitions (intervention group) with control communities. Ten years after implementing community coalitions, higher sports engagement and more time spent on PA were reported in the intervention group.…”
Section: Discussionmentioning
confidence: 99%
“…To account for this critique a component of our broader project included a study that explored the question of whether communities with a CSP had higher levels of sport participation than control communities without a CSP. The results of this study showed that program communities noted an average sport participation rate of 61.3 %, which was about 20 % higher than the control communities [ 19 ]. This present study tries to pinpoint the reasons and the underpinning processes of partnerships that build capacity on the three different levels and consequently help in explaining these proximal outcomes of the CSP.…”
Section: Methodsmentioning
confidence: 99%
“…A prior study showed that this CSP was related to higher levels of sport participation [ 19 ]. In communities where the CSP was implemented, 61.3 % of adults engaged in sport, whereas in similar communities, without the CSP, this was only 42.4 %.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation